2021
DOI: 10.2147/lra.s290224
|View full text |Cite
|
Sign up to set email alerts
|

Quadratus Lumborum Blocks in Nephrectomy: A Narrative Review

Abstract: The quadratus lumborum block is a novel truncal block where local anaesthetic is injected adjacent to the quadratus lumborum muscle. It is used for caesarean sections, hip arthroplasty, gynecologic surgery, colectomy, and recently nephrectomy. To date, there are no reviews that outline the efficacy and performance of the quadratus lumborum blocks in patients receiving laparoscopic nephrectomy. The objective of this project was to outline the current available data from both clinical trials along with case seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 45 publications
(73 reference statements)
0
8
1
Order By: Relevance
“…However, the Epidural group had significatively fewer rescue analgesics than QLB. This result is contrary to a human study [ 21 ] in which patients receiving quadratus lumborum block for nephrectomies had reduced opioid requirements, reduced pain scores, and improved side effects relative to other analgesic modalities such as epidurals.…”
Section: Discussioncontrasting
confidence: 97%
“…However, the Epidural group had significatively fewer rescue analgesics than QLB. This result is contrary to a human study [ 21 ] in which patients receiving quadratus lumborum block for nephrectomies had reduced opioid requirements, reduced pain scores, and improved side effects relative to other analgesic modalities such as epidurals.…”
Section: Discussioncontrasting
confidence: 97%
“…They concluded that QLB significantly reduced postoperative opioid consumption by 43% and significantly prolonged time to rescue opioid therapy. Another important narrative review of QLB in open nephrectomy was consistent with reduced opioid consumption postoperatively (7) .…”
Section: Discussionmentioning
confidence: 97%
“…[11] Recently, in addition to TAP block, quadratus lumborum block, retrolaminar block, and erector spinae plane block have been found to be useful in patients undergoing laparoscopic nephrectomy. [30–33]…”
Section: Discussionmentioning
confidence: 99%